Green Transportation Policy In Indonesia and Its Future Challenges - Adly, Emil; Khairunnissa, Siti; Laksamana, Boy (Mahadi: Indonesia Journal of Law, 2024)
Green transportation policies in Indonesia have shown positive progress in reducing the environmental impact of the transportation sector. However, there are still major challenges that need to be overcome to achieve sustainable development goals in transportation. Limited infrastructure, the high cost of green vehicles, and the level of public awareness that needs to be increased are the main focus of this effort. The government needs to expand infrastructure, particularly in building electric vehicle charging stations across Indonesia, to support wider adoption of green vehicles. Active support from the private sector is also important in accelerating the development of environmentally friendly transportation technologies. In addition, consistent and sustainable policy development will provide certainty to investors and industry players to invest in green technology. The high initial cost of green vehicles is a major barrier for consumers. Therefore, appropriate fiscal incentives and subsidies are needed to make green vehicles more affordable and increase their attractiveness in the market. Raising public awareness about the long-term benefits of green transportation is also a crucial strategy through effective education campaigns. With strong collaboration between the government, the private sector, and the active participation of the public, Indonesia can overcome these challenges and achieve green transformation.